Association of Community Characteristics as Measured by Social Deprivation Index Score with Prenatal Care and Obstetrical Outcomes - Sassin, Alexa M.; Osterlund, Natalie; Sangi-Haghpeykar, Haleh; Aagaard, Kjersti (American Journal of Perinatology, 2025)
We aimed to determine the relationships between socioeconomic disadvantage, as measured by the Social Deprivation Index (SDI), and prenatal care (PNC) utilization, obstetrical outcomes, and neonatal complications.All spontaneously conceived singleton deliveries of nulliparous gravida with residence zip code available (n = 4,786) were identified in a population-based database. Deliveries were assigned SDI scores based on preconception zip code. SDI scores (1–100) are a composite measure of seven community demographic characteristics of poverty, education, transportation, employment, and household composition. SDI scores were categorized into quartiles and grouped for analysis (Q1 [n = 1,342], Q2 + 3 [n = 1,752], and Q4 [n = 1,692]) with higher scores indicative of greater disadvantage. Statistical analysis was performed using a generalized linear mixed method.Among our cohort, gravida in the lowest (least-deprived) SDI quartile (Q1) were older, had lower prepregnancy body mass indices, and were more likely to receive PNC from a physician specializing in Obstetrics and Gynecology. Gravida residing in the highest (most-deprived) SDI quartile (Q4) attended fewer prenatal visits (mean [standard deviation] 11.17 [2.9]) than those living in Q1 (12.04 [2.3], p < 0.0001). Gravida in Q4 were less likely to receive sufficient PNC compared with those in Q1 (52 vs. 64.2%, p < 0.0001) and were more likely to fail to achieve appropriate gestational weight gain (GWG) (19.6 in Q4 vs. 15.9% in Q1, p < 0.01). No significant differences in composite maternal (CMM) or neonatal morbidity (CNM) were associated with SDI quartile.Outer quartile social deprivation was associated with higher proportions of primigravida not meeting recommendations for GWG and attending fewer prenatal visits, but it did not affect CMM or CNM. Improving care access and providing nutritional support to all gravida are likely important steps toward health equity.
Keywords: social determinants of health; neighborhood vulnerability; prenatal care utilization; composite maternal morbidity; composite neonatal morbidity; gestational weight gain; maternal mental health